2017
DOI: 10.1097/gme.0000000000000857
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically assessed hot flashes and endothelial function among midlife women

Abstract: Objective Hot flashes are experienced by most midlife women. Emerging data indicate that they may be associated with endothelial dysfunction. No studies have tested whether hot flashes are associated with endothelial function using physiologic measures of hot flashes. We tested whether physiologically-assessed hot flashes were associated with poorer endothelial function. We also considered whether age modified associations. Methods 272 nonsmoking women reporting either daily hot flashes or no hot flashes, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 58 publications
0
21
1
3
Order By: Relevance
“…(10) More recently, the SWAN investigators reported that severe hot flashes were “robustly” associated with higher intima media-thickness (IMT), an important marker for subclinical cardiovascular disease. (25) In the Women's Health Initiative Study (WHI), more frequent and more severe symptoms were associated with an increased risk of hypertension, cardiovascular disease and stroke. (11)…”
Section: Symptomsmentioning
confidence: 99%
“…(10) More recently, the SWAN investigators reported that severe hot flashes were “robustly” associated with higher intima media-thickness (IMT), an important marker for subclinical cardiovascular disease. (25) In the Women's Health Initiative Study (WHI), more frequent and more severe symptoms were associated with an increased risk of hypertension, cardiovascular disease and stroke. (11)…”
Section: Symptomsmentioning
confidence: 99%
“…One such mechanism is endothelial dysfunction. 41 In addition, multiple studies report evidence of endothelial vascular dysfunction in migraineurs, including abnormalities in the control of vascular tone and impaired ability for endothelial repair. 40 Women experiencing hot flashes have poorer endothelial function compared with those who do not experience hot flashes, even after controlling for cardiovascular risk factors.…”
Section: Potential Trait Endothelial Vascular Abnormality In Migraineursmentioning
confidence: 99%
“…40 Women experiencing hot flashes have poorer endothelial function compared with those who do not experience hot flashes, even after controlling for cardiovascular risk factors. 41 In addition, multiple studies report evidence of endothelial vascular dysfunction in migraineurs, including abnormalities in the control of vascular tone and impaired ability for endothelial repair. 42 According to the largest metaanalysis of genome-wide association studies of migraine to date, migraine-associated genes are mainly involved in vascular and smooth muscle functions.…”
Section: Potential Trait Endothelial Vascular Abnormality In Migraineursmentioning
confidence: 99%
“…Есть данные об ассоциации приливов с метаболическими нарушениями [35], в том числе с инсулинорезистентностью [36], гиперхолестеринемией и гипертриглицеридемией [37]. Однако степень риска при этом варьирует в зависимости от многих факторов, в том числе от тяжести и вида нейровегетативной симптоматики, а также времени и причины наступления менопаузы [38,39]. Тем не менее учитывая, что сосудистая дизрегуляция занимает центральное место в развитии проявлений вазомоторных симптомов, а также является важным фактором прогрессирования ССЗ и других заболеваний, приливы могут рассматриваться потенциальными маркерами их риска.…”
Section: вазомоторные симптомы как индикаторы риска развития заболеваunclassified